HUBUNGAN PERILAKU ORANG TUA DENGAN KEJADIAN OBESITAS PADA ANAK PRASEKOLAH (3-5 TAHUN) DI TAMAN FLORA KOTA SURABAYA - Pipit Festy, Pipit Festy (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2012)
Obesity is a global problem that happened by the world society in both the developed and developing countries including Indonesia. Based on the first survey, it shows that a lot of preschool children who are obese, and one reason is their knowledge, attitudes and parents behavior. The purpose of this research is to know that there is relation between knowledge, attitude and parents behavior with the obesity incident.The corelasical analytic research design is using Cross sectional perspektif, using Simple random sampling method. Samples were taken by 44 respondents that are parents with preschool children who visit the flora garden of Surabaya city in June 2011. The research was taken using a questionnaire and observation. After itâs tabulated, the data were analyzed using multiple logistic regression test.This research shows that the parentsâs knowledge with a value of Î± = 0.027 <0.05, parentss attitudes to the value of Î± = 0.016 <0.05 and parentss behavior with a value of Î± = 0.007 <0.05, itâs means there is a relation. It can be concluded that there is a relationship of knowledge, attitudes and parents behavior with the obesity incident in preschool children.Based on the results of the research, the society should increase their knowledge, attitudes and behaviors regarding the provision of nutrition intake and activities appropriate for preschool children to the childs weight can be well controlled so that obesity in preschool children can be prevented as early as possible through improved education of health personnel.Â Keywords: Knowledge, attitude, behavior of parents, the obesity incident